Occupational mobility of Brazilian immigrant women in Spain - Parella Rubio, Sónia; Cavalcanti, Leonardo (Sociedad y Economía, 2010)
This paper focuses on the study of occupational mobility of Brazilian immigrant women in Spain from a gender perspective. The goal of the research is to establish the main characteristics among this group of migrants, as well as consider, through a qualitative approach, the factors (external and internal; structural and personal) that condition their occupational mobility trajectories within Spanish society. The results presented are part of a wider research project Los inmigrantes brasileños en la estructura socioeconómica española financed by Permanent Observatory for Immigration (Ministry of Labour and Immigration), carried out during 2008-2009.